DOTS for temporary workers in the agricultural sector. An exploratory study in Tuberculosis case detection - M Clarke (AOSIS, 2003)
This study was conducted in the Boland health district of the Cape Winelands of South Africa where there is a high tuberculosis incidence and prevalence. A survey conducted on 211 farms in the study district during 1998, reported that 65% (n = 9042) of all workers on these farms, were temporarily employed. Temporary farm workers live in communities either within or on the outskirts of the boundaries of the Boland health district, from where they are transported to work daily.